Negative experiences in psychotherapy from clients' perspective: A qualitative meta-analysis - Vybíral, Zbyněk; Ogles, Benjamin M.; Řiháček, Tomáš; Urbancová, Barbora; Gocieková, Veronika (Psychotherapy research, 2024)
A considerable number of clients report adverse or unwanted effects of psychological treatments. This study aimed to synthesize the findings of qualitative studies focused on what clients perceive as negative experiences in psychotherapy. A database search was conducted to find primary studies, and a qualitative meta-analysis was used to aggregate the findings on the kinds of negative experiences psychotherapy clients reported. A total of 936 statements were extracted from 51 primary studies and categorized into 21 meta-categories, some of which were further divided into subcategories. These meta-categories covered clients' experiences, which fell into four broad clusters: therapists' misbehaviour, hindering aspects of the relationship, poor treatment fit, and negative impacts of treatment. Clients' negative experiences of psychotherapy are a vast and heterogeneous area, the breadth of which is not captured by any single study. By synthesizing the findings of many primary studies, this meta-analysis represents the most comprehensive summary of these experiences to date.